Effect of TIG welding current variation on the tensile strength of stainless steel 304 welded joints (Program Studi Teknik Mesin Fakultas Teknik Universitas Pasundan, 2026)
This study investigates the effect of TIG welding current variation on the tensile strength characteristics of stainless steel 304 welded joints. The research is motivated by the need to optimise welding parameters to ensure reliable mechanical performance and minimise variability in welded structures used in industrial applications. Inadequate control of welding current may lead to unstable heat input, affecting weld penetration, microstructural homogeneity, and joint strength. Therefore, this study aims to evaluate the influence of welding current on tensile performance through an experimental and statistical approach. Welding was conducted at two current levels, 115 A and 125 A, followed by tensile testing in accordance with ASTM E8 standards. Statistical analyses, including descriptive statistics and one-way ANOVA, were applied to assess the significance of current variation. The results indicate that the average tensile strength increased from 28.33 MPa at 115 A to 42.87 MPa at 125 A, with reduced data variability at higher current. ANOVA confirmed a significant effect of welding current (p < 0.05). These findings suggest that higher heat input within an optimal range improves weld integrity and mechanical consistency. The study concludes that appropriate current selection enhances joint reliability, offering practical implications for welding parameter optimisation and future research on microstructural and process parameter interactions